2011
DOI: 10.1111/j.1600-6143.2011.03609.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic and Gender Related Differences in the Risk of End-Stage Renal Disease After Living Kidney Donation

Abstract: There is limited data pertaining to the risk of EndESRD rates for LKDs overall and for Black, White, male and female donors compared favorably to the ESRD incidence in the general population. The LKD ESRD rate was nearly five times higher for Blacks than for Whites and two times higher for males than females. However, these ethnic and gender-related differences were similar to those previously reported for ESRD in the general population. Our findings do not show an increase in the risk of ESRD for LKDs and sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
114
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(119 citation statements)
references
References 11 publications
3
114
0
2
Order By: Relevance
“…Reported postdonation ESRD rates are higher for blacks and Hispanics than for whites, male patients, and younger donors. However, the ethnicity-and sex-related differences are similar to those observed in the general population with two kidneys (48,49).…”
Section: Risk For Esrdmentioning
confidence: 48%
See 2 more Smart Citations
“…Reported postdonation ESRD rates are higher for blacks and Hispanics than for whites, male patients, and younger donors. However, the ethnicity-and sex-related differences are similar to those observed in the general population with two kidneys (48,49).…”
Section: Risk For Esrdmentioning
confidence: 48%
“…In the largest series to date, Cherikh et al reported that 126 former donors have been put on the waiting list for transplantation in the United States (48). This may underestimate the rate of ESRD in that some developing ESRD may no opt for transplantation or have received an LD transplant.…”
Section: Risk For Esrdmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, male sex, baseline hypertension, and African American race were independently associated with perioperative complications in multivariable models. These same characteristics have also been associated with increased risk of later medical complications, ESRD, and death within other donor cohorts (10)(11)(12). Whether early complications play a mediating role in the long-term risks needs to be defined in data sources (or primary studies) capturing longitudinal outcomes.…”
mentioning
confidence: 99%
“…Recently, Muzaale and colleagues reported a higher risk of devel oping ESRD among kidney donors than among healthy non-donors [28]. Previous studies had shown no significant effect of kidney donation on the risk of developing ESRD [29,30]. The study by Muzaale et al [28] has received considerable criticism regards to the methodology used and limitations of the control groups, such as disparities between the decades in which the control and donor population data were extracted.…”
Section: Advantages Of Living Donor Transplantationmentioning
confidence: 80%